AN OVERVIEW OF SELF-REGULATED LEARNING STRATEGY IN CRITICAL READING FOR UNIVERSITY STUDENTS (RETAIN, 2020)
University students are the learners in the higher level of education. It makes them be independent learners and have more responsibility to be successful learners which regulated by themselves. Since, they are independent learners, they have an authority to set their own goals, deciding suitable strategies to be used, controlling the strategies they are used, evaluating whether the strategies are effective or not, dealing with their emotion, environment, and motivation. The regulation of those strategies can be called as self-regulated learning strategy. However, the strategies used in SRL are different from one student to another. That is why the term of the successful learners and less successful learners occur. To be a successful learner, university students have to comprehend the reading skill in order to gain much information. University students not only have to comprehend their reading ability but also reading critically because they have more responsibilities processing the information for academic purposes and the information most of from the texts. Thus, this paper provides that self-regulated learning strategy promotes students’ critical reading in order to be successful learners. Key Words: self-regulated learning (SRL), university students, critical reading